ROSELLE FLOWER (HIBISCUS SABDARIFFA) IN THE TREATMENT OF HYPERTENSION IN POSTPARTUM MOTHERS - Nikmah Jalilah Ritonga; Onny Setiani; Umaroh Umaroh; Kamilah Budhi R; Faisal Amri (Belitung Nursing Journal, 2017)
Background: Roselle flower (Hibiscus sabdariffa) has been used as a food and herbal drinks, in hot and cold beverages, as an herbal medicine. Objective: To examine the effect of consuming roselle dried flower petals on changes in maternal hypertensive blood pressure during postpartum period. Methods: This was a quasi-experimental study with non-equivalent control group design conducted in 2016. There were 30 samples recruited using consecutive sampling with 15 samples in an intervention group and a control group. Data were analyzed using paired t-test to know the difference of blood pressure value before and after intervention in the intervention and control group, and independent t-test to determine the difference of blood pressure decrease between intervention and control group. Mann-Whitney and Wilcoxon test were also conducted for data analysis. Results: Findings showed that there were statistically significant differences in systolic and diastolic blood pressure values before and after intervention in the intervention and the control group with p-value 0.000 (<0.05) with systolic blood pressure decrease was 5 mmHg and diastolic was 5.33 mmHg. Additionally, there was a significant effect in the duration of healing in the intervention group with p-value 0.000 (<0.05), with the average duration of healing was 2 days. Conclusion: There were significant effects of dried petals of rosella flowers (Hibiscus sabdariffa) brewed with 200 ml of hot water with temperature 90oC in lowering blood pressure, and there were significant differences in systolic and diastolic blood pressure and duration of healing between the intervention group and the control group of mothers who consumed antihypertensive drugs. The results of this study can be applied by midwives in postpartum care with the cases of hypertension. It is expected that this intervention can help the healing process more quickly through a combination of antihypertensive medicines and sedated petals of rosella flowers.